2001
DOI: 10.1007/s004310100788
|View full text |Cite
|
Sign up to set email alerts
|

Management of ingested foreign bodies in childhood and review of the literature

Abstract: Recommendations for management of children presenting with a history of suspected accidental ingestion of a foreign body for the community paediatrician are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
197
4
29

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(269 citation statements)
references
References 19 publications
(27 reference statements)
8
197
4
29
Order By: Relevance
“…10 Even though a large number of them will also pass through the gastrointestinal tract once past the gastroesophageal junction; nevertheless it is preferable to observe them in the hospital for possible need for immediate abdominal exploration should bleeding or features of perforation occurs. 11 Two patients among hairpin group who were put on conservative treatment because of late presentation developed signs of peritonitis and computerized tomography scan abdomen showed pin outside intestines and free fluid in peritoneal cavity, were operated by midline abdominal incision. Hairpin in both these cases was retrieved and peritoneal cavity containing bowel content mixed with reactionary fluid was thoroughy washed.…”
Section: Discussionmentioning
confidence: 99%
“…10 Even though a large number of them will also pass through the gastrointestinal tract once past the gastroesophageal junction; nevertheless it is preferable to observe them in the hospital for possible need for immediate abdominal exploration should bleeding or features of perforation occurs. 11 Two patients among hairpin group who were put on conservative treatment because of late presentation developed signs of peritonitis and computerized tomography scan abdomen showed pin outside intestines and free fluid in peritoneal cavity, were operated by midline abdominal incision. Hairpin in both these cases was retrieved and peritoneal cavity containing bowel content mixed with reactionary fluid was thoroughy washed.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of them are under 5 years, with a peak between 6 months and 3 years. A study from Belgium reported that the most frequent FB in children under 15 are in descending order: coins (27%), needles-pins (16%), buttons (13%), fish/chicken bones (12%), large food boluses (12%) and jewels (6%) and that the higher frequency is observed in boys (11). Among ingested objects lodged in the esophagus, coins are almost two thirds, followed by meat boluses and some dentures.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the batteries in the stomach only need to be removed if the patient is symptomatic or if the battery does not pass the pylorus within 48 hours, which may occur if it is larger than 15 mm in diameter [1,4,33]. Other physicians recommend that ingested batteries should be removed whenever possible [10,34].…”
Section: Batteriesmentioning
confidence: 99%
“…Pediatric surgeons are usually the primary physicians managing these children. Otolaryngologists, radiologists, and pediatric gastroenterologists are also commonly involved in the care of these patients [9,10].…”
Section: Introductionmentioning
confidence: 99%